Partial and impartial ethical reasoning in health care professionals - Kuhse, H. (Journal of medical ethics, 1997)
OBJECTIVES: To determine the relationship between ethical reasoning and gender and occupation among a group of male and female nurses and doctors. DESIGN: Partialist and impartialist forms of ethical reasoning were defined and singled out as being central to the difference between what is known as the "care" moral orientation (Gilligan) and the "justice" orientation (Kohlberg). A structured questionnaire based on four hypothetical moral dilemmas involving combinations of (health care) professional, non-professional, life-threatening and non-life-threatening situations, was piloted and then mailed to a randomly selected sample of doctors and nurses. SETTING: 400 doctors from Victoria, and 200 doctors and 400 nurses from New South Wales. RESULTS: 178 doctors and 122 nurses returned completed questionnaires. 115 doctors were male, 61 female; 50 nurses were male and 72 were female. It was hypothesised that there would be an association between feminine subjects and partialist reasoning and masculine subjects and impartialist reasoning. It was also hypothesised that nurses would adopt a partialist approach to reasoning and doctors an impartialist approach. No relationship between any of these variables was observed.